2005
DOI: 10.1103/physrevlett.95.237210
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Localized Holes in Manganite Thin Films with Atomic Resolution

Abstract: The magnetic and transport behaviors of manganites are critically related to the spatial distribution and correlation of doped holes. Using in situ scanning tunneling microscopy, we have imaged both occupied and unoccupied states simultaneously in a hole-doped (La(5/8-0.3)Pr0.3)Ca(3/8)MnO3 epitaxial thin film grown by laser molecular beam epitaxy. Doped holes localized on Mn4+ ion sites were directly observed with atomic resolution in the paramagnetic state at room temperature. In contrast to a random distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 31 publications
2
38
0
Order By: Relevance
“…As in prior STM/STS work on electronically inhomogeneous manganites, [24][25][26][27][28] contiguous nanoscale regions of similar differential conductance are evident, conductive clusters forming in an insulating matrix. The extent of this inhomogeneity is reinforced by Fig.…”
Section: (001)mentioning
confidence: 63%
“…As in prior STM/STS work on electronically inhomogeneous manganites, [24][25][26][27][28] contiguous nanoscale regions of similar differential conductance are evident, conductive clusters forming in an insulating matrix. The extent of this inhomogeneity is reinforced by Fig.…”
Section: (001)mentioning
confidence: 63%
“…4c,e). Although the Ca doping ratio in our experimental system case is 3/8, it has been observed that this kind of CE-type state still exists 22,23 . The only difference is that the CE-type state in 3/8 Ca-doping system is weaker and easier to be disturbed owing to the doping offset to its optimized half doping, which will benefit the emergence of ferromagnetic edge states.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of a reconstruction indicates that indeed no oxygen-vacancy induced reconstructions exist at the surface. Atomically ordered single crystalline films have been produced routinely using similar procedures in our lab 26,27 . After growth the sample was transferred to a connecting variable temperature scanning tunneling microscopy (STM) chamber without breaking ultra-high vacuum.…”
Section: Resultsmentioning
confidence: 99%